Survival benefit of renal transplantation in octogenarians. Issue 11 (27th September 2020) - Ravichandran, Bharath R.; Sparkes, Tracy M.; Masters, Brian M.; Thomas, Beje; Demehin, Moses; Bromberg, Jonathan S.; Haririan, Abdolreza
Abstract: Background: Elderly patients are the fastest growing population requiring renal replacement therapy. As previous studies have shown a survival benefit of kidney transplantation compared to dialysis for end‐stage renal disease, we sought to evaluate if this survival benefit extends to octogenarians. Methods: This was a single‐center retrospective cohort study of renal allograft recipients ≥80 years transplanted from 1999 to 2014 who were compared to patients listed during the same period that did not proceed to transplantation. A secondary matched group was selected from the UNOS transplant waitlist database. The primary outcome was patient survival. Secondary outcomes included graft survival and rejection incidence. Results: Thirty‐three transplanted patients were compared to 71 patients waitlisted at our center and 66 patients from the UNOS database. Patients in the study group were transplanted 20.8 ± 16.1 months after listing. Patient survival was 87.8% at 6 months and 1 year and 71.4% at 3 years. Kidney transplantation was associated with a significant decrease in the risk of death after listing (HR: 0.22, CI: 0.11‐0.45, P < .001). Conclusion: With escalating life expectancy, kidney transplantation is a suitable treatment option in eligible octogenarians.